Dielectric measurement based microstrip transmission line - Ikhsan, Fatin Hamimah (2019)
The measurement of complex dielectric properties of materials at radio frequency is very important especially in the research fields, such as material science, microwave circuit design, absorber development, biological research, etc. Dielectric measurement is important because it can provide the electrical and magnetic characteristics of the materials, which proved useful in many research and development fields.The proposed technique present a simple microstrip transmission line method for the broadband radio frequency characterization of dielectric constant of non-dispersive materials. A microstrip line having impedance other than 50 Ω is designed and material under test is used as the substrate. The impedance mismatch between a non-50 Ω characteristic impedance of the microstrip line and 50 Ω coaxial to microstrip connectors generates significant reflection/transmission at the input ports. The mismatch between the input impedance and port is used to extract the dielectric constant of the substrate. For experimental validation, the microstrip trace is sticked on the test substrate which are FR4, Teflon and Roger 5880. During the measurement, the microstrip line is connected to vector network analyser through SMA connectors. It is found that this technique introduce error of 10.83%, 7.53% and 21.32% for FR4, Teflon and Roger 5880 respectively. On the other hand, the comparison with the experimental measurement shows 13.5%, 52.95% and 31.40% of error for FR4, Teflon and Roger 5880 respectively. The future research, can focus on measuring the dielectric properties of dispersive material including its loss factor material based on Kramers-kronig relationship.